Fractional calculus: d'oú venons-nous? Que sommes-nous? Où allons-nous? - Machado, J. A. Tenreiro (2017)
Along with the presentations made during this Round Table, we include here some contributions by the participants sent afterwards and also by few colleagues planning but failed to attend. The intention of these discussions was to continue the useful traditions from the ﬁrst conferences on Fractional Calculus (FC) topics, to pose open problems, challenging hypotheses and questions “where to go”, “how to save and improve the prestige of FC”, to share opinions and try to ﬁnd ways to resolve them.